Kalaupapa place names, Waikolu to Nihoa - Clark, John R. K., 1946- (University of Hawai'i Press, 2018)
In Kalaupapa Place Names, John Clark presents a unique history of the leprosy settlement on Moloka'i, based on his meticulous research of more than three hundred Hawaiian-language newspaper articles. He first assembled an extensive list of familiar and long-forgotten place names associated with the Kalaupapa peninsula and then searched for them in the online repository of Hawaiian-language newspapers. With translation assistance by Iāsona Ellinwood and Keao NeSmith, he discovered articles that show a community of Hawaiians from every island except uninhabited Kaho'olawe. Their stories reveal an active community with its members trying to live their lives as normally as possible in the face of a debilitating disease. The first section of the book contains newspaper articles arranged under an alphabetical listing of place names. The second section organizes the material into chronological segments, from before the establishment of the Kalaupapa Settlement to the death of Mother Marianne Cope in 1918. These two sections are followed by a collection of kanikau or lamentations, interviews with Kalaupapa residents, and a list of Hawaiian language newspapers. Introductory paragraphs for groupings of newspaper articles assist the reader in visualizing the physical landscape and understanding the history and significance of a particular location. The poetry of the Hawaiian language is evident throughout the translations, especially in the kanikau.